How the tapeworm Hymenolepis diminuta affects zinc and cadmium accumulation in a host fed a hyperaccumulating plant (Arabidopsis halleri) - Jankovská, I; Sloup, V; Száková, J; Langrová, I; Sloup, S (Environmental science and pollution research international, 2016)
The effects of plant-bound zinc (Zn) and cadmium (Cd) on element uptake and their interactions in a parasite-host system were investigated in a model experiment. Male Wistar rats were divided into four groups (C, P, TC and TP). Groups TC and TP were infected with the rat tapeworm Hymenolepis diminuta. Groups C and TC were fed a standard rodent mixture (ST-1) and received 10.5 mg of Zn per week, while groups P and TP were fed a mixture supplemented with the Zn- and Cd-hyperaccumulating plant Arabidopsis halleri at a dosage of 236 mg Zn/week and 3.0 mg Cd/week. Rats were euthanized after 6 weeks, and Cd and Zn levels were determined in rat and tapeworm tissue. The results indicate that tapeworm presence did have an effect on Cd and Zn concentrations in the host tissue; the majority of tissues in infected rats had statistically significant lower Zn and Cd concentrations than did uninfected rats. Tapeworms accumulated more zinc and cadmium than did the majority of host tissues. This important finding confirms the ability of tapeworms to accumulate certain elements (heavy metals) from the host body to their own body tissues. Thus, tapeworms can decrease heavy metal concentrations in host tissues.
Keywords: Plant; Metals, Heavy; Accumulate; Diet; Rat; Tapeworm; krysa rodu Rattus; Zinc; zvířata; zinek; potkani Wistar; Arabidopsis; Hymenolepis diminuta; Cadmium; těžké kovy; Rats, Wistar; Male; dieta; kadmium; Rats; Animals; mužské pohlaví